Magnetic resonance and anisotropy in multilayer Co/Cu (111) system - Kutko, K.V.; Kaplienko, A.I.; Nikolova, E.P.; Anders, A.G.; Zorchenko, V.V.; Stetsenko, A.N. (Functional Materials, 2008)
The angular dependences of FMR spectra for the multilayer system [Co (8 Å)/Cu (dcu) (111)]₂₀ are studied. The values of internal effective field are measured, and the parameters of spatial nonuniformities of the system as a function of copper nonmagnetic layer thickness are calculated. The parameters values are found to increase with a number of Cu layers. The dependences are treated qualitatively in terms of the model taking account of interface roughness. The degree of roughness is increasing with grown nonmagnetic layer thickness. Досліджено кутові залежності спектрів ФМР у багатошаровій системі [Co (8 Å)/Cu (dcu) (111)]₂₀. Виміряно значення внутрішнього ефективного поля та розраховано залежності параметрів просторових неоднорідностей системи від товщини немагнітного шару міді. Виявлено, що значення цих параметрів зростають зі збільшенням кількості шарів Cu. Якісний опис цих залежностей виконано у рамках моделі, що враховує шорсткість інтерфейсів, ступінь якої збільшується при збільшенні товщини немагнітних шарів. Исследованы угловые зависимости спектров ФМР в многослойной системе [Co (8 Å)/Cu (dcu) (111)]₂₀. Измерены значения внутреннего эффективного поля и рассчитаны зависимости параметров пространственных неоднородностей системы от толщины немагнитного слоя Cu. Обнаружено, что значения этих параметров возрастают по мере увеличения количества слоев меди. Качественное описание этих зависимостей выполнено в рамках модели, учитывающей шероховатость интерфейсов, степень которой увеличивается при увеличении толщины немагнитных слоев.